Fanfikcja, sposoby radzenia sobie i „przenoszenie się" do innej rzeczywistości - Rokicka, Kaja (Studia Etnologiczne i Antropologiczne, 2023)
The development and popularization of social media have increased social anomie, as exemplified by dissemination of fake news, stereotypes, hate, ostracism, social isolation, and ubiquitous fear of missing out. As a result, members of society are more exposed to witnessing and reading of tragedies than previously. The youth of today try to find some methods to “drown out” the reality, even if the methods they use were to be effective only temporarily. That is how, in some cases, people become addicted to and dependent on any form of mass media: social media and fiction (such as video games, books, TV shows, movies or cartoons, etc.). The present article attempts to answer the question of why the young people seek closure aided by fiction, and to provide examples to illustrate it.